Republic of Kosovo : Fourth Review Under the Stand-By Arrangement. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2013)
This staff report on the Republic of Kosovo's Fourth Review under the Stand-By Arrangement discusses macroeconomic and financial policies. Banking-sector soundness indicators have remained largely unchanged. The revenue shortfall owed to a mix of lower than programmed customs receipts, and delays in receiving transfers from the sales of telecommunication licenses, and lignite royalties. The shortfall was only partially compensated by higher domestic tax collection, and the earlier than expected receipt in dividends from Post and Telecom of Kosovo. Passage of the rules-based fiscal framework would be a key step toward ensuring fiscal sustainability in the longer term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet